Techno-creativity: the implementation of DVFx as creative support tools among filmmakers in Malaysia, India & Australia - Hasrul Hashim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Previously, the use of digital visual effects (DVFx) only serves merely to fix or modify the damage or harmful elements in the post-production. Still, there are differences between improving the work and the creative effects in work. Subtracting part of the image can often be seen as a form of creativity in generating new image elements. DVFx is also seen as a form of creative effects. It is a fascinating field of study on 'adverse impact' or 'creative impact' in film production. Creative impact in the production process of film is likely to lead to a new assessment on the aspects of 'creativity.' The occurrence of technological changes that involve creative work will undoubtedly lead to a shift in creativity. Technology and creativity or techno-creativity are likely to represent a new creative possibility and measurement in film production using creative software as a support tool. This paper discusses the findings derived from in-depth interviews conducted with filmmakers, visual effects artists and supervisors from Malaysia, India, and Australia on implementing DVFx as creative support tools. The finding shows that DVFx functions as a techno-creative device in two main areas: ideation and implementation. These two aspects involve using DVFx as a tool for transforming the ideas and the imagination of a filmmaker into a reality on the screen. In other words, DVFx has acted as creative support tools (CST) to increase techno-creativity, especially in the area of visual presentation.